Chronic inflammation during osteoarthritis is associated with an increased expression of CD161 during advanced stage. (14th May 2019) - Sachdeva, Meenakshi; Aggarwal, Aditya; Sharma, Ravi; Randhawa, Arpan; Sahni, Daisy; Jacob, Justin; Sharma, Vinit; Aggarwal, Anjali
Abstract: Increasing evidence suggests a role of inflammation during the pathogenesis of osteoarthritis (OA). The local and systemic inflammation was studied in 33 patients of different KL grades, grade2 (n = 11), grade3 (n = 6) and grade4 (n = 16). The levels of cytokines, adipokines and matrix metalloproteinases (MMPs) were measured in serum and synovial fluid (SF) by flow cytometry and ELISA, respectively. The frequency of T cells and CD161 expression was measured by flow cytometry. The levels of IL‐1β, IL‐6 and IL‐10 were significantly higher in sera and SF of patients with OA as compared to healthy control's serum. Higher levels of MMP9 and leptin and lower levels of adiponectin were observed in SF as compared to serum. The MMP9 in SF and MMP13 levels in serum and SF decreased in KL grade 4 cases. In these patients, higher levels of leptin and lower levels of adiponectin were observed in SF versus patients of lower grades. There was increased infiltration of CD8+ T cells in SF of OA cases with decreased frequency in grade 4 cases. The expression of CD161 on T cells was significantly higher in SF than peripheral blood with significant upregulation in grade 4 patients. The CD161 expression had significant positive correlation with IL‐17 in the serum of patients. The ROC curves of CD161 expression significantly distinguished grade 2 and grade 4 patients. Collectively, an elevated CD161 expression on T cells in circulation and synovial compartment clearly distinguished lower and higher grade patients warranting studies to assess its role as a contributing factor towards OA progression.